Effect of post-shooting bunch spray of growth hormone and fertilizer on yield attributing characters of banana: Effect of growth hormone and fertilizer on banana (SAARC Journal of Agriculture, 2022)
An experiment was conducted at a commercial banana orchard in Chitwan to find out the best chemical to increase the yield and quality of banana during the fruit development stage. The research was laid out in a randomized complete block design (RCBD) with seven treatments and three replications. The treatment included plant growth hormones GA3 and Naphthalene acetic acid (NAA)@ 50 ppm and 100 ppm each. Similarly, Sulphate of Potash (SOP) was applied @ 1.5% and 2%. The first spray was applied soon after the bunch had completely opened, and the second spray was applied 15 days later. The effect of these chemicals on yield and quality parameters was observed. The result revealed that the application of GA3 @ 100 ppm increased the length, girth and weight of the bananas. Likewise, the highest weight of the third hand of the banana was also observed in GA3 @ 100 ppm, whereas minimum physiological loss in the weight of the finger and maximum pulp to peel ratio was observed in SOP @ 1.5%. Analyzing all these observed parameters, GA3 @ 100ppm was found to be the most suitable growth hormone to increase the overall yield while SOP @ 1.5%SAARC J. Agric., 20(1): 157-169 (2022)